Review of economic studies : being a collection of review articles of substantial academic interest (Lagos : University of Lagos, 1974)
This reviews examines the relative economics roles of the public and private sectors in development and debunk existing orthodoxies and ends up with what appears to be a restatement of "the political economy of development".
asm; 06/03/19
Loans
Keywords: Economics; Finance; Nigeria